Research competencies in Peruvian higher education: a mixed-methods evaluation - Carmen Lily Winchez Aylas; Patricia Bejarano Álvarez (International Journal of Evaluation and Research in Education (IJERE), 2026)
Research participation among Peruvian university students remains low, which limits the systematic development of research competencies needed for academic and professional training. This review identifies effective pedagogical strategies to strengthen research skills in Peruvian higher education and compares them with international trends. Following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, we analyzed 52 peer-reviewed studies published between 2017 and 2024. The evidence shows that flipped learning, collaborative learning, research workshops and seedbeds, project-based learning (PBL), and academic mentoring consistently improve students’ research competencies, including critical thinking, methodological rigor, and scientific communication. These approaches also increase autonomy, engagement, and sustained work on authentic research problems. Overall, student-centered and practice-oriented strategies can strengthen research training and support a sustainable research culture in Peruvian universities.